Evaluation of Sitra’s Sustainability Solutions theme – Part 2 Insights for possible future priorities - Hjelt Mari; Ahvenharju Sanna; Lauttamäki Ville; Järvinen Jasmin; Moisio Matleena; Jyrälä Minna; Saukkonen Tuuli (Sitra, 2025)
The Finnish Innovation Fund Sitra commissioned this forward-looking outcome evaluation of its Sustainability Solutions theme (2015-2022) in late 2022. During the evaluation period, the theme had a broad overall objective to ensure and accelerate adaptation to the earth’s carrying capacity through an ecological reconstruction of society and everyday life. Gaia, together with the Finland Futures Research Centre of the University of Turku, completed the evaluation in June 2023.
The evaluation was implemented with an innovative mixed-method approach, integrating two adapted foresight methods: horizon scanning and a Delphi panel. While the primary objective of the evaluation was to evaluate the outcomes of the portfolio, the foresight phase aimed to identify and evaluate the most significant future phenomena around ecological sustainability, which could be used to validate the relevance and timeliness of Sitra’s strategic choices during the evaluated period and for strengthening Sitra’s future-oriented approach to the thematic work.
The results and the process supported the evaluation well by producing insights around future phenomena that Sitra could work with and also by validating some of the strategic choices Sitra has already made. Two significant and systemic phenomena were identified. These were: 1) the intertwined health of humans and nature (planetary health); and 2) nature-positive and regenerative economic models. These findings echo with the choices made in Sitra’s latest projects. The Delphi panel participants considered Finland to have the potential to act as a global piloting platform for many solutions. And Sitra was regarded as being the right type of organisation to act as a global visionary and exporter of futures thinking.